MODEL TRANSPORTASI UNTUK DISTRIBUSI PANGAN POKOK DI WILAYAH TERPENCIL KABUPATEN BIREUEN - VIVI ASBAR; Nur Amalia Hasma (Pendidikan Matematika Universitas Almuslim, 2026)
This study aims to analyze an effective transportation model for distributing staple food to remote areas in Bireuen Regency, Aceh Province. The distribution of staple food in remote regions often faces various obstacles such as poor road infrastructure, limited transportation fleets, and high logistics costs. This research uses a descriptive analysis method to describe the actual distribution conditions, as well as mathematical modeling using the transportation method approach to determine optimal solutions in reducing costs and increasing delivery efficiency. Data were obtained from relevant agencies and field observations in several sub-districts classified as hard-to-reach areas. The results show that the application of an appropriate transportation model by considering supply capacity, demand, and per-unit distribution costs can significantly reduce total logistics expenses. Moreover, this model can assist policymakers in planning a fairer and more equitable distribution strategy, thereby supporting food security in remote areas. This study recommends the integration of information technology and cross-sector collaboration as a long-term strategy for sustainable food distribution in Bireuen Regency.